Relationship Between the Electroglottographic Signal and Vocal Fold Contact Area - Hampala, Vít; Garcia, Maxime; Švec, Jan G; Scherer, Ronald C; Herbst, Christian T (Journal of voice, 2016)
OBJECTIVE: Electroglottography (EGG) is a widely used noninvasive method that purports to measure changes in relative vocal fold contact area (VFCA) during phonation. Despite its broad application, the putative direct relation between the EGG waveform and VFCA has to date only been formally tested in a single study, suggesting an approximately linear relationship. However, in that study, flow-induced vocal fold (VF) vibration was not investigated. A rigorous empirical evaluation of EGG as a measure of VFCA under proper physiological conditions is therefore still needed. METHODS/DESIGN: Three red deer larynges were phonated in an excised hemilarynx preparation using a conducting glass plate. The time-varying contact between the VF and the glass plate was assessed by high-speed video recordings at 6000 fps, synchronized to the EGG signal. RESULTS: The average differences between the normalized [0, 1] VFCA and EGG waveforms for the three larynges were 0.180 (±0.156), 0.075 (±0.115), and 0.168 (±0.184) in the contacting phase and 0.159 (±0.112), -0.003 (±0.029), and 0.004 (±0.032) in the decontacting phase. DISCUSSIONS AND CONCLUSIONS: Overall, there was a better agreement between VFCA and the EGG waveform in the decontacting phase than in the contacting phase. Disagreements may be caused by nonuniform tissue conductance properties, electrode placement, and electroglottograph hardware circuitry. Pending further research, the EGG waveform may be a reasonable first approximation to change in medial contact area between the VFs during phonation. However, any quantitative and statistical data derived from EGG should be interpreted cautiously, allowing for potential deviations from true VFCA.
Keywords: Deer; Signal Processing, Computer-Assisted; vysoká zvěř; Excised hemilarynx; audiovizuální záznam; Video Recording; laryngoskopie; hlasové řasy; Female; počítačové zpracování signálu; zvířata; High-speed imaging; vibrace; elektrodiagnostika; reprodukovatelnost výsledků; Vocal Cords; ženské pohlaví; fonace; Reproducibility of Results; Vibration; Vocal fold contact area; Laryngoscopy; Animals; biomechanika; Biomechanical Phenomena; Electrodiagnosis; Electroglottography; Phonation